Defect Studies in Thin-Film SiO2 of a Metal-Oxide-Silicon Capacitor Using Drift-Assisted Positron Annihilation Lifetime Spectroscopy - Ricardo Helm; Werner Egger; Catherine Corbel; Peter Sperr; Maik Butterling; Andreas Wagner; Maciej Oskar Liedke; Johannes Mitteneder; Michael Mayerhofer; Kangho Lee; Georg S. Duesberg; Günther Dollinger; et al. (Nanomaterials)
This work investigates the impact of an internal electric field on the annihilation characteristics of positrons implanted in a <semantics>180(10)<mspace width="3.33333pt"></mspace>nm</semantics> SiO2 layer of a Metal-Oxide-Silicon (MOS) capacitor, using Positron Annihilation Lifetime Spectroscopy (PALS). By varying the gate voltage, electric fields up to <semantics>1.72<mspace width="3.33333pt"></mspace>MV/cm</semantics> were applied. The measurements reveal a field-dependent suppression of positronium (Ps) formation by up to <semantics>64%</semantics>, leading to an enhancement of free positron annihilation. The increase in free positrons suggests that vacancy clusters are the dominant defect type in the oxide layer. Additionally, drift towards the SiO2/Si interface reveals not only larger void-like defects but also a distinct population of smaller traps that are less prominent when drifting to the Al/SiO2 interface. In total, by combining positron drift with PALS, more detailed insights into the nature and spatial distribution of defects within the SiO2 network and in particular near the SiO2/Si interface are obtained.